Pengaruh Kompensasi dan Motivasi Terhadap Produktivitas Kerja Melalui Kepuasan Kerja Sebagai Variabel Intervening (Studi Kasus pada Karyawan Bagian Produksi PT. Estika Pulau Mas Tegal) - Edi Sumarno; Ari Pradhanawati; Naili Farida (Universitas Diponegoro, 2013)
The purpose of this study was to determine the effect of compensation, motivation, and job satisfaction on employee productivity at PT. Estika Pulau Mas Tegal. The population in this study are 275 employees and a sample of 100 employees. Measurement scale using a Likert scale. The method of analysis used is proportionate sampling. In the analysis of the data using simple linear regression, regression test, and path analysis using SPSS 16.0. Based on the results of the calculations indicate that the compensation affect on job satisfaction by 5.2%. Motivation affect the job satisfaction of 7.3%. Job satisfaction variables influence the labor productivity by 13.2%. Compensation affect on labor productivity by 13.2%. Motivation affect labor productivity by 11.3%. Simultaneously, compensation and motivation affect the job satisfaction by 7.3%. Compensation, motivation, and job satisfaction affects the labor productivity by 49.1%. Conclusions obtained in this study in which each variable compensation, motivation, job satisfaction has a positive effect on work productivity. Suggestion in this study that the remuneration should be done as agreement that has been agreed before, it’s once a week. Working facilities such as production machinery operations must be considered for eligibility, the machines that are old should be replaced with new ones so that production can be increased.